Asymetric information, reputation building, and bureaucratic inefficiency - Carlsen, Fredrik (1994)
The paper shows that asymmetric information about preferences is a possible source of bureaucratic inefficiency. The analysis is based on an application of the reputation model of Kreps and Wilson to a bureaucracy model in the Niskanen tradition. We consider a public bureau which is funded by a government sponsor. If the bureau has incomplete information about the sponsor's opportunity cost of funds and the sponsor does not know the bureau's aversion to effort, both agents may choose to engage in reputation manipulation in order to induce the opponent to contribute more to the production of public services. We show the existence of a perfect Bayesian equilibrium where cost and allocation inefficiency may p revail for a considerable period of time. - Reproduced
Keywords: Civil service; Bureaucracy